If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = -84 + 10x Reorder the terms: 12 + 6x = -84 + 10x Solving 12 + 6x = -84 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 6x + -10x = -84 + 10x + -10x Combine like terms: 6x + -10x = -4x 12 + -4x = -84 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -4x = -84 + 0 12 + -4x = -84 Add '-12' to each side of the equation. 12 + -12 + -4x = -84 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = -84 + -12 -4x = -84 + -12 Combine like terms: -84 + -12 = -96 -4x = -96 Divide each side by '-4'. x = 24 Simplifying x = 24
| 12x-42=114 | | 13-6x=5-8x | | 7p-(3+4)=-2(2p-1)+10 | | 5(x-4)+3-9x=6-(2x+5)+8x | | 56+8x=128 | | 5x-2(x+1)=9 | | -16t^2+16t^2+896= | | 53-10x=17+8x | | 4x-44=0 | | -17r=-170 | | 4x+83=-7 | | 11x+1=12-4 | | z-20=15 | | 15(y-4)= | | 85000=.9x | | 3x-4(2x+1)=-(x-3)+6x+8 | | 7-7x-3x=37 | | 31=-8(5x-4) | | 11c=55 | | 6s-9-5s=-35 | | (999)=6 | | -29=5+3(v+6) | | 5-(3x-4)=3(2x+7)-8x | | 5x+12=9x-19 | | 12-6x=36+2x | | -5(-2x-7)=55 | | y^7-x=248832 | | 9r-8=7r+18 | | 12x-14=5x+14 | | 4cos^2(3x)-1=0 | | Z=10+14i | | 2x+-2=2x-3 |